2017
DOI: 10.1515/fsmu-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

The chipping cost of wood raw material for fuel in Estonian conditions

Abstract: Irdla, M., Padari, A., Kurvits, V., Muiste, P. 2017. The chipping cost of wood raw material for fuel in Estonian conditions. -Forestry Studies | Metsanduslikud Uurimused 66, 65-74. ISSN 1406-9954. Journal homepage: http://mi.emu.ee/forestry.studies Abstract. In Estonia up to now the producers of wood fuels have not yet adequately analysed the production and transport costs although it is known that the share of these costs form up to half of the fi nal price of wood chips or hog fuel. With this in mind the goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
(5 reference statements)
0
12
2
1
Order By: Relevance
“…To our knowledge, there are no other studies that have gathered long-term data from so many chipping contractors, and the few available studies tap into the records of State companies and cooperatives, which often benefit from the existence of a formal administration office and a centralized infrastructure [22].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…To our knowledge, there are no other studies that have gathered long-term data from so many chipping contractors, and the few available studies tap into the records of State companies and cooperatives, which often benefit from the existence of a formal administration office and a centralized infrastructure [22].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In 2019, Spinelli et al [18] indicated that chipper repair and maintenance may represent between 1.5% and 29% of total production cost. They declared that repair and maintenance costs are complicated to calculate as the rate, scale, and severity of breakdowns are inherently variable [25], and different repairmen or operators may record various cost figures for the same maintenance activity [26][27][28]. Many factors could increase the frequency and severity of failures and reduce safety, such as careless equipment storage, poor preventive maintenance, and low quality of prior repairs [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, with the accelerated growth of computer science and emerging Internet of Things (IoT) technologies, maintenance strategies have revolutionized from preventive maintenance (schedule-based maintenance) to predictive maintenance (PdM). Remaining Useful Life (RUL) is the time left for a machine/component to offer its operative capabilities before a crash [25]. The maintenance planner or decision-maker use this metric to plan the actual time that machinery needs maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The basic ones include: a cylindrical chipper [1], a drum chipper [2], a disc chipper [3], a hammer chipper [4], or a spiral chipper [5]. Chippers for the industrial production of biomass, with high capacity (indicated in scientific publications on the power range from 130 kW to 900 kW [6]), have the wood chips outlet system based on the forced motion of the cutting mechanism [2,3,[7][8][9][10][11]. Chippers used on urban areas for tree care in parks, gardens, and by-road surfaces are low power machines (Figure 1).…”
Section: Introductionmentioning
confidence: 99%